(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
The present research include studying the structural ,linear and nonlinear optical properties for organic laser dye: doped with (PVA) polymer and (Ag)nano particles for using it in field of nonlinear optics. Many properties of organic laser dyes can be improved and enhanced by doping with polymer and nanoparticles materials, which are favorable for practical applications.Thin films have better linear and non-linear spectral optical properties as compared to solutions. And samples prepared from dyes doped with polymers and nanomaterials have better nonlinear optical properties compared to samples prepared from single dyes . The results indicate that the optical power limiting threshold is inversely related to the solution concentration the prepared thin films of mixture laser dyes with ratio(4:1) doped with PVA polymer and Ag nano particles give spectral , linear and nonlinear optical parameters high as compared with other mixing ratios.Where the highest value of the quantum efficiency (96%) and the highest value of the nonlinear refractive index and the nonlinear absorption coefficient (12.68×10-3 cm2/mW) and (6.125 cm/mW) were obtained, respectively. The results indicate that all samples of pure and doped dyes and its mixture (solutions and thin films) could be employed as a suitable medium for a variety of optoelectronic applications, including optical power limiting and active laser medium in liquid lasers.